Postoperative Pain Management: Evaluating the Role of Multimodal Analgesia - Archana Gautam; Chetan Pande; Meghana Pande (Journal of Pharmacy and Bioallied Sciences)
Background: Effective postoperative pain management is essential for enhancing recovery and improving patient outcomes. Multimodal analgesia (MMA) combines different analgesic approaches to optimize pain control while reducing opioid dependence. This study evaluates the effectiveness of MMA in managing postoperative pain across various surgical procedures. Objectives: To assess the impact of multimodal analgesia on postoperative pain relief, opioid consumption, and associated side effects. Methods: A quasi-experimental study was conducted with 60 patients divided into a study group (n=30) receiving MMA and a control group (n=30) receiving standard pain management. Pain levels were assessed using the Visual Analog Scale (VAS) at 6, 12, and 24 hours post-surgery. Opioid consumption and the incidence of side effects were also recorded. Results: The study group reported significantly lower VAS pain scores at all time points compared to the control group. Additionally, opioid consumption was reduced, with fewer opioid-related side effects observed in the MMA group. Conclusion: Multimodal analgesia effectively reduces postoperative pain, minimizes opioid use, and decreases associated side effects, supporting its broader implementation in clinical pain management strategies.